Influence of Additives on the Structure and Properties of Gypsum-Cement-Pozzolanic Binder - Ekaterina Potapova; Aung Kyaw Nyein; Elena Tsvetkova; Hans-Betram Fischer (Research Developments in Science and Technology Vol. 5, 2022)
Gypsum binders are not characterized by high strength and water resistance. This does not allow the use of these binders at high humidity. Modification of the structure of gypsum-cement-pozzolanic binder allows you to expand the range of gypsum binders for creating dry building mixes and structural elements of low-rise buildings. The aim of the study was to develop a durable and water-resistant gypsum binder. The conducted studies have shown that in the presence of functional additives, the nature of the crystallization of hydrate neoplasms changes, which leads to a change in the properties of the cured binder. The study of the influence of individual and complex additives on the properties of the gypsum-cement-pozzolanic binder made it possible to develop strong, water-resistant gypsum binders.